2015
DOI: 10.1111/risa.12286
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis, Dominant Factors, and Robustness of the ECETOC TRA v3, Stoffenmanager 4.5, and ART 1.5 Occupational Exposure Models

Abstract: Occupational exposure modeling is widely used in the context of the E.U. regulation on the registration, evaluation, authorization, and restriction of chemicals (REACH). First tier tools, such as European Centre for Ecotoxicology and TOxicology of Chemicals (ECETOC) targeted risk assessment (TRA) or Stoffenmanager, are used to screen a wide range of substances. Those of concern are investigated further using second tier tools, e.g., Advanced REACH Tool (ART). Local sensitivity analysis (SA) methods are used he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 35 publications
3
40
0
Order By: Relevance
“…[5,12] In general, the ventilation multiplier Considering that Stoffenmanager and the ART are classified as higher tier exposure assessment tools, [5,17] both are recommended by ECHA for regulatory exposure assessment, [22] and that Stoffenmanager has alone over 32,000 users, [3] the errors is general ventilation multipliers should not be ignored. The studies [5,[22][23][24][25][26][27][28][29][30] concerning the tools evaluation, validation, applicability, and sensitivity analysis should be revised and corrected before the tools are used in regulatory risk assessment or before implementing them to tools combining different exposure models, such as a Translation Tool to Support the Use of Regulatory Occupational Exposure Models (TREXMO; [31] see also letter to the editors, [31][32][33] ) SUN decision support system, [34] or risk governance tools developed in caLIBERAte. [35] In our opinion, the regulatory exposure modeling should rely only on mathematical models following general physical principles, such as conservation of mass, rather than conceptual models based on non-physical models or exposure determinants.…”
Section: Discussionmentioning
confidence: 99%
“…[5,12] In general, the ventilation multiplier Considering that Stoffenmanager and the ART are classified as higher tier exposure assessment tools, [5,17] both are recommended by ECHA for regulatory exposure assessment, [22] and that Stoffenmanager has alone over 32,000 users, [3] the errors is general ventilation multipliers should not be ignored. The studies [5,[22][23][24][25][26][27][28][29][30] concerning the tools evaluation, validation, applicability, and sensitivity analysis should be revised and corrected before the tools are used in regulatory risk assessment or before implementing them to tools combining different exposure models, such as a Translation Tool to Support the Use of Regulatory Occupational Exposure Models (TREXMO; [31] see also letter to the editors, [31][32][33] ) SUN decision support system, [34] or risk governance tools developed in caLIBERAte. [35] In our opinion, the regulatory exposure modeling should rely only on mathematical models following general physical principles, such as conservation of mass, rather than conceptual models based on non-physical models or exposure determinants.…”
Section: Discussionmentioning
confidence: 99%
“…5 [ 2 _ T D $ D I F F ] Further work is underway to clarify acceptance of the changes to PROC 7 from PROC 10 in this study.…”
Section: _ T D $ D I F F ] Work Compared To Proc [ 1 3 _ T D $ D I F mentioning
confidence: 85%
“…We selected Stoffenmanager® from the available mechanistic models, based on our review of past validations and sensitivity studies that compared common mechanistic tools. Overall, estimates by the Stoffenmanager approach yield more accurate estimates than those from the other models of the same tier and remain conservative when compared to higher tier models, which sometimes underestimate the exposure (Koppisch, Schinkel, Gabriel, Fransman, & Tielemans, ; Landberg, Axmon, Westberg, & Tinnerberg, ; Riedmann, Gasic, & Vernez, ; Schinkel et al., ; Spinazzè et al., ). Navigation of Stoffenmanager quantitative exposure estimation module is briefly outlined in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…One potential variation in the prior specification could arise from between‐user variations in assigning parameters for Stoffenmanager. Past reliability surveys have found that among parameters used in Stoffenmanager and similar models, the parameter “type of activity/handling” tends to be the most sensitive, yet it also tends to have larger user variations in selection (Landberg et al., ; Riedmann et al., ; Schinkel et al., ). We varied “handling type” by one order above and one order below the original setting, to characterize the impact of prior sensitivity according to Stoffenmanager reliability (Fig.…”
Section: Methodsmentioning
confidence: 99%